Synergistic Expertise Supporting Pedagogical Development and Innovation - Cooperberg, Andrea; Argento, Amanda; Turgeon, Chantal; Regan, Susan; Hackett, Teresa; Brown, Douglas; Prévost, Nathalie; Crossland, Constance (QUESCREN Education and Vitality Forum 2023, 2023)

An Independent Report of the History Experts Committee On the Provincial History of Québec and Canada Program and Approved English Textbooks - Commission scolaire English-Montreal / English Montreal School Board (2018)
In September 2017, the Ministry of Education implemented a revised Secondary III and IV compulsory History of Québec and Canada program. This program raised a number of issues that became of concern to the English Montreal School Board (EMSB). Given these concerns, the EMSB commissioned an independent History Experts Committee to review the content of this program as well as the Ministry-approved English-language textbooks. The following is a summary of the findings of this Committee

Écoles québécoises en ligne : Un monde de possibilités pour l'éducation en langue anglaise - Advisory Board on English Education (2014)
En 1996, la Commission de l’éducation en langue anglaise (CELA) a déposé un mémoire sur l’intégration des technologies de l’information et de la communication (TIC) dans les écoles anglophones dans lequel elle souligne les besoins particuliers de ces établissements, notamment en milieu rural, et formule des recommandations sur des sujets comme l’accessibilité de ces nouveaux outils, le soutien aux enseignants et l’organisation scolaire. Les membres actuels de la CELA constatent l’ampleur et le rythme des progrès technologiques depuis 1996, mais continuent d’avaliser en principe le contenu du document antérieur, forts d’une conviction profonde que la technologie reste subordonnée à la pédagogie. Il n’en reste pas moins que la technologie présente dans la classe a changé à un rythme qui était inimaginable à cette époque. Les changements sont qualitatifs autant que quantitatifs et appellent donc une discussion entre toutes les parties prenantes sur son interaction avec la pédagogie, au vu de l’évolution de notre compréhension de l’enseignement et de l’apprentissage. Par ailleurs, les problèmes que posent aux écoles et aux centres de formation anglophones la composition et la dispersion de la population ainsi que la distance se font plus aigus et nécessitent des solutions ingénieuses si l’on veut que les diplômés soient prêts pour le XXIe siècle, et les solutions que peuvent fournir les TIC méritent discussion. Le présent mémoire porte sur la situation générale, mais aussi sur les questions qui touchent particulièrement le système d’éducation en langue anglaise du Québec. Il contient un ensemble de recommandations destinées à guider le Ministère dans la formulation de ses orientations.

Québec Schools On Line : Opportunities for English-Language Education - Advisory Commitee for English-Speaking Quebecers (2014)
In 1996, The Advisory Board on English Education (ABEE) prepared a brief on the integration of technology into English language schools, noting the particular needs of these schools, especially in rural areas, and making recommendations on accessibility, teacher support, and school organization, among other issues. The current Board notes how much—and how quickly— the technology has changed since 1996 but, based on its strongly held belief that technology is subordinate to pedagogy, it endorses in principle the content of this earlier document. Yet the technology available for classroom use has changed, it has done so at a speed unimaginable in 1996, and done so qualitatively as well as quantitatively, making it imperative that a broad-based discussion of technology in teaching take place as part of our changing understanding of teaching and learning. In addition, the problems in English language schools and centres caused by demographics, distance and dispersion have become more acute and more in need of ingenious solutions so that their graduates are prepared for the 21st century, and potential solutions to these problems through Information and Communications Technologies (ICT) merit discussion. This brief addresses both the general issues and those pertinent to the English education system in Québec, and includes a set of recommendations to help in the formulation of MELS orientations.

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL) (2002)

A Statement from Quebec Federation of Home and School Associations to the Superior Council of Education on the State of the Condition of Teaching in the Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1984)
Quebec Federation of Home and School Associations (QFHSA) is a parent group, working as volunteers at the school, provincial and national levels. QFHSA takes particular pride in the fact, that over the last forty years, parents, as volunteers, have seconded the schools' efforts to provide assistance in areas of school life, to upgrade or enhance the school's environment and, thereby, benefit the students. As an adjunct to direct involvement at the school level, though its resolutions addressed, over the years, to various levels involved in the educational process, QFHSA has pinpointed areas its members felt needed either more funding, changing, support, introduction, etc., as the case may be. These will be referred to specifically later on.

A Position Paper on Measurement & Evaluation to Department of Education Province of Quebec - Quebec Federation of Home and School Associations (QFHSA) (1974)
The Quebec Federation of Home and School Associations welcomes the opportunity to express its concerns on the subject of Measurement and Evaluation. It is pleased that the Depatment of Education desires to assume a greater role in facilitating communication among "the various members of the educational community" as well as providing them with services to aid them in their individual responsibllities.

Brief on CEGEPS Presented by Quebec Federation of Home & School Associations to the Superior Council of Education - Quebec Federation of Home and School Associations (QFHSA) (1973)
Our Committee is composed of sixteen members who have been actively involved in Home & School over the years and have children in or going into CEGEP system of education. In order to become more knowledgeable about the five English language CEGEPS (Dawson, Vanier, John Abbott, Champlain Regional, and Marionopolis Colleges) our Committee arranged interviews with the Academic Deans, teachers, and student representatives.

Report of Sex Education Committee - Quebec Federation of Protestant Home & School Associations (1967)
The term "sex education" as used in the terms of reference has been interpreted by the committee to mean education in which sexual, biological and physiological facts are only disclosed in the full context of human relations. It must be made clear at the outset therefore, that sex education, in our opinion, cannot consist of less than education in Human Relations in which sexual growth is seen as part of the whole growth of the individual and in which basic sexual facts are discussed in the context of the growing boy and girl in their development into manhood and womanhood.

In Survival Mode : Adult Education Teachers Experience of Covid-19 and their Use of Digital Technologies - Bowles, Emilie

Empowering Adult Learners : Supporting Students in Adult Education and Vocational Training - Roy, Lucie

Literacy Across the Curriculumedia Focus - The Centre for Literacy of Quebec (CFL)